Attitudes Toward Punishment, Organizational Commitment, and Cynicism: A Multilevel Analysis of Staff Responses in a Juvenile Justice Agency - Kras, Kimberly Raye (Criminal justice and behavior, 2019)
Staff commitment to agency goals is important in juvenile justice settings, where the mission oscillates between the often-competing goals of rehabilitating youth and punishing them. Although prior research considers how staff characteristics relate to commitment to, and/or cynicism about, criminal justice organizations, less work examines these relationships in juvenile justice settings, and even less examines the effects of staff attitudes toward punishment. The current study assesses the influence of rehabilitative and punitive attitudes on organizational commitment and cynicism in a juvenile justice agency (n = 204). Multilevel analyses evaluating staff members within organizational units reveal that staff holding more traditional (punitive) attitudes are significantly and positively associated with cynicism, whereas staff holding rehabilitative values demonstrate greater commitment to the agency. Findings suggest attitudes toward punishment play an important role in staff commitment to, and cynicism about, justice organizations, which may affect workers’ adherence to organizational policies and goals.